3
this is because
![x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
and
y
are all separate variables (also
![x^{3} y](https://tex.z-dn.net/?f=x%5E%7B3%7D%20y)
combines into one variable)
<em>Answer:</em>
<em>63°</em>
<em>Step-by-step explanation:</em>
<em>Hi there ! </em>
<em>ABCD parallelogram => ∡A = ∡C</em>
<em>13x - 41 = 6x + 15</em>
<em>13x - 6x = 15 + 41</em>
<em>7x = 56</em>
<em>x = 56 : 7</em>
<em>x = 8</em>
<em>∡C = 6×8 + 15 = 48 + 15 = 63°</em>
<em>Good luck !</em>
The answer is 87. it was quite simple